Answer:
Parallel
Step-by-step explanation:
Answer:
B. 23x-10
Step-by-step explanation:
Answer:
y= -4x^2 + 15x - 14
Step-by-step explanation:
A parabola is always in the form y = ax^2 + bx + c.
Substitute each point to produce different equations:
-14 = 0a + 0b + c = c
so c = -14
-3 = a1^2 + b1 + c = a + b - 14
so a + b = 11
0 = a2^2 + b2 + c = 4a + 2b -14 = 0
so 4a + 2b = 14
if we double a + b = 11 we get 2a + 2b = 22
Subtract this from 4a + 2b = 14 and we get 2a = -8 so a= -4 and b = 11 - a = 15
We don't need to use the (3,5) points as we have all the information we need.
Answer:
- 77x + 42
Step-by-step explanation:
note that (f ○ g)(x) = f(g(x)
Substitute x = g(x) into f(x)
f(g(x))
= f(7x - 4)
= - 11(7x - 4) - 2
= - 77x + 44 - 2
= - 77x + 42